Zagociguat prevented stressor-induced neuromuscular dysfunction, improved mitochondrial physiology, and increased exercise capacity in diverse mitochondrial respiratory chain disease zebrafish models - Leonard Burg; Heeyong Yoon; Min Peng; Peter Germano; Emily Reesey Gretzmacher; Rui Xiao; Vernon E. Anderson; Eiko Nakamaru-Ogiso; Eiko Nakamaru-Ogiso; Marni J. Falk; Marni J. Falk (Frontiers in Pharmacology)
BackgroundZagociguat (zag) is a CNS-penetrant, soluble guanylate cyclase (sGC) stimulator that has been evaluated in phase 2a, with phase 2b ongoing, clinical studies of primary mitochondrial disease (PMD) subjects with mitochondrial encephalomyopathy, lactic acidosis, and stroke-like episodes syndrome (MELAS). To explore its utility in a broader array of PMDs and secondary mitochondrial disorders, we performed prfeclinical modeling of zag across larval and adult zebrafish models with biochemical deficiencies in diverse respiratory chain (RC) complexes or dihydrolipoamide dehydrogenase (Dldh).MethodsZag was evaluated for tissue uptake, gross toxicity, protection from RC toxin-induced brain death, neuromuscular dysfunction, heartbeat loss, and biochemical dysfunction in transgenic or toxin-exposed zebrafish with mitochondrial enzyme deficiencies in complex I (ndufs2−/− or rotenone-exposed wild type (WT)), complex IV (surf1−/− or azide-exposed WT), multiple RC complexes (fbxl4−/−), or pyruvate dehydrogenase complex (dldh−/−). Zag effects were also studied on the whole-body oxygen consumption capacity (MO2) and swimming activity of WT and complex IV disease adult zebrafish.ResultsSimilar zag levels were observed in adult brains and tail muscle. No morphological or functional toxic effects of zag were observed on larvae viability. Zag provided neuromuscular protection in complex I deficient genetic and pharmacologic inhibitor models. In complex IV deficient models, prevention from brain death occurred at 100 nM zag in high-dose azide-exposed WT larvae; however, no rescue of swimming or neuromuscular phenotypes in low-dose azide-exposed surf1−/− larvae was observed. A total of 100 nM zag rescued MO2 and maximum swimming speed in adult surf1−/− zebrafish. Larval swimming activity was also preserved with 10 nM zag treatment in azide-stressed fbxl4−/− larvae but not at 10 nM, 100 nM, or 1 µM zag in dldh−/− larvae. Zag (10 nM) enhanced complex I enzyme activity that is suggestive of mitochondrial biogenesis and key aspects of mitochondrial physiology in azide-exposed surf1−/− and fbxl4−/− larvae.ConclusionPreclinical evaluation of zag demonstrated its safety, significant protection of neuromuscular dysfunction and/or acute RC stressor-induced decompensation, and improved mitochondrial physiology across multiple different genetic and/or pharmacologic models of RC-deficient PMD. Thus, zag may yield therapeutic potential for an array of diseases with mitochondrial dysfunction beyond MELAS, potentially including Leigh syndrome spectrum disorder and primary mitochondrial myopathies.